The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1038/321588a0
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution of peroxyacetyl nitrate

Abstract: Nitrogen oxides (NOx) have a central role in the chemistry of the atmosphere, especially in key processes relating to ozone, hydroxyl-radical (OH) and acid formation. High reactivity of NOx (lifetime of 0.5-2 days) precludes hemispheric-scale transport and it has been proposed that non-methane hydrocarbons present in the troposphere can transform NOx into its organic forms principally as peroxyacetyl nitrate (PAN). PAN is highly stable in the colder regions of the middle and upper troposphere and can provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(84 citation statements)
references
References 17 publications
2
81
0
1
Order By: Relevance
“…These high concentrations can probably be explained by long-range transport of PAN-enriched air from lower latitudes or higher altitudes. Several airborne and ship-based "eld experiments have demonstrated that PAN mixing ratios are normally below 10 pptv in the MBL of the Southern Hemisphere (Singh et al, 1986(Singh et al, , 1998Rudolph et al, 1987;MuK ller and Rudolph, 1992;Schultz et al, 1999). In contrast, recent investigations onboard RV Polarstern showed that over the South Atlantic mean PAN concentrations of 60 pptv north of 493S can occur .…”
Section: Methods and Instrumentationmentioning
confidence: 99%
“…These high concentrations can probably be explained by long-range transport of PAN-enriched air from lower latitudes or higher altitudes. Several airborne and ship-based "eld experiments have demonstrated that PAN mixing ratios are normally below 10 pptv in the MBL of the Southern Hemisphere (Singh et al, 1986(Singh et al, , 1998Rudolph et al, 1987;MuK ller and Rudolph, 1992;Schultz et al, 1999). In contrast, recent investigations onboard RV Polarstern showed that over the South Atlantic mean PAN concentrations of 60 pptv north of 493S can occur .…”
Section: Methods and Instrumentationmentioning
confidence: 99%
“…The photocatalytic efficiency (ξ) was calculated according to equation (1). The catalyst selectivity for nitrate (S) was calculated according to equation (2).…”
Section: Photocatalytic Performancementioning
confidence: 99%
“…NOx gases are not only toxic in their own right but they contribute to the formation of other toxic atmospheric pollutants, such as ground level ozone, PAN (peroxyacytyl nitrate), etc. [1][2][3] . Consequently, EU and EPA guidelines for maximum atmospheric NO and NO 2 concentrations have been set but these are regularly exceeded in urban centers because the largest contribution to NOx gases in the urban atmosphere comes from automotive emissions [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…oxidants may arise in atmosphere for peroxyacetyl nitrate [34,35]. which is rather an unstable compound, we used mchloroperoxybenzoic acid, which is stable for 10 min in solution, to study oxidation of Met residues in a-l-PI.…”
Section: Cy-i-pimentioning
confidence: 99%